Consumers’ safety of some selected ready to eat and street vended foods in Wudil, Kano state as determined by microbial content - Garba, Abubakar Ibrahim (Eureka, Life Sciences, 2023)
Because of their cost, affordability, availability and simplicity to prepare, ready-to-eat foods are highly consumed in all over Nigeria, therefore critical to Nigerians’ health. This research aimed at ascertaining the consumers’ safety in terms of microbial load in ready-to-eat sell on the street Awara (Steamed Cowpea Beans Slurry) and Moin-moin (Bean pie) sold in three different vending locations retailed to the students of Aliko Dangote University of Science and Technology Wudil, Kano state Nigeria. Total of 24 samples consisting of equal quantity of Awara (Bean pie) and Moin-moin (Steamed Cowpea Bean Slurry) were collected from three different location in Wudil town and analyzed for total aerobic bacteria, fungi and Staphyococcus count. Seven different species of microorganism of health concern were identified to include Micrococcus spp, Staphylococcus aureous, Bacillus spp., Klebsiella spp., Mucor, Rhizophus stoonifer and Aspergillus flavus. The total mean of the aerobic bacteria, fungi and Staphylococcus count across all the location in all the samples were found to be withing the tolerable range with the standard set by the International Commission for Microbial Specification for Foods (ICMSF) and Food and Environmental Hygiene Standard (FEHD) as well as the South Wales Food Authority Standards for ready-to-eat foods. Higher microbial counts were founds on Moin-moin sample and this may be attributed to its high moisture content which is found to range from 64.2 to 70.0 %. The comparison of this research finding with international standard justified the safety of consumers and concludes the acceptability of these foods as safe to eat even though the presence of microorganisms such as Aspergilus spp. has been found to pose serious public health issue such as aflatoxin intoxication